Derivación de valores económicos de la producción de leche de bovinos en la parroquia Ignacio Flores del cantón Latacunga, provincia de Cotopaxi. utilizando funciones de beneficio. - Guanuche Pacheco, Mónica Abigail (2022)
In the parish of Ignacio Flores, there is a small number of people engaged in dairy production, despite the high density of hectares, because the people of the sector have little knowledge about the bovine genetic improvement and the benefit that this brings, the economic values of milk production of cattle in the parish were derived, using profit functions, from this the necessary aspects were selected for a possible improvement of cattle genetics and profitability. We used surveys that were socialized with the inhabitants of the parish to describe their production system, which is based on terms of feeding, breed, cattle health, milk testing among other aspects, in addition to mastitis testing (CMT). Most of the producers participating in the project lack knowledge that would allow them to keep efficient records of production and reproduction of the cattle they manage. It was also observed that all the project partners do not keep cost control, either due to lack of knowledge or lack of importance in the subject. It was evident that there is concern about the cost of milk, which is no more than 0.45 pennies, indicating that there is a loss for small producers in the parish. Studies of milk quality showed that there are animals that do not meet the established parameters (1028 to 1033 g/ml), adding a poor quality of total solids in the milk. When testing for CMT, 89.2% of cows show a possible resilience to this disease. Selection criteria were selected to be exploited in this area, such as adaptability to the environment in which the animals develop, looking for small animals, milk density and weight gain. The information gathered in the project is a baseline for genetic selection criteria, concomitant with the economic utility of cattle production systems, preferring the cattle with the best performance for genetic improvement.